Field-Deployed Extruded Seed Pellets Show Promise for Perennial Grass Establishment in Arid Zone Mine Rehabilitation - Stock, Emma; Standish, Rachel J.; Muñoz-Rojas, Miriam; Bell, Richard W.; Erickson, Todd E. (Frontiers in Ecology and Evolution, 2020)
Current methods of mine rehabilitation in the arid zone have a high failure rate at seedling emergence largely due to limited availability of topsoil and low water-holding capacity of alternative growth substrates such as mining overburden and tailings. Further, seedlings have consistently failed to emerge from seeds sown on the soil surface using traditional broadcasting methods. Seed pellets, formed by extruding soil mixtures and seeds into pellets, can potentially increase soil water uptake through enhanced soil-seed contact and thereby improve seedling emergence. We tested an extruded seed pelleting method in a three-factor field experiment (i.e. different pellet-soil mixtures, organic amendments, and simulated rainfall regimes) in north-western Australia. Given the observed lack of seedling emergence from broadcast seeds, the aims of the experiment were to assess: (i) the use of pellets to promote native seedling emergence and establishment and; ii) the soil physico-chemical and microbiological changes that occur with this method of rehabilitation. The effects of pellet-soil mixtures, organic amendment, and rainfall regime on seedling emergence and survival of three native plant species suggest trade-offs among responses. Pellets made with a 1:1 blend of topsoil and a loamy-sand waste material had the highest seedling emergence, while 100 % topsoil pellets had lower emergence probably because of hardsetting. Triodia pungens (a native grass) survived to the end of the experiment while Indigofera monophylla and Acacia inaequilatera (native shrubs) emerged but did not survive. Adding an organic amendment in the extruded pellet inhibited Triodia seedling emergence but increased soil microbial activity. Overall, extruded pellets made from a 1:1 blend showed promise for the establishment of Triodia seeds and beneficially, incorporates mine waste overburden and lesser amounts of topsoil. Further research is needed to improve pelleting production and to test the applicability of the method at scale, for different species and other ecosystem types.